OPTIMALISASI FUNGSI PERWAKILAN MASYARAKAT DALAM PEMBANGUNAN DI KEDAH MALAYSIA - Lahamid, Sadriah; Zahrin, Zuriana; Fisdian, Dita; Syahrudin, Syahrudin (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
Community representation is synonymous with its position in a country's political institutions. Kedah is a sultanate which is part of Malaysia, even though it is a sultanate, Kedah has a Representative or Legislative Body consisting of multi-party institutions, the institution is called the Kedah State Invitation Council. 36 Members of the State Invitation Board were elected to represent each constituency of the state of Kedah. Its functions and authorities are almost the same as Indonesia's, namely dealing with regulations (legislation), deliberating the state budget, and supervising the implementation of Kedah's development. Because Kedah is a sultanate, the Sultan's influence is still very strong. ADUN's position is not very functional, especially in supervising development. The service was held in Mukin Singkir Village, Yan Kedah which was attended by the Kedah community and students from UUM Kedah. This service in the form of counseling invites the Kedah community to further enhance their role in development, especially the women of Kedah. It is hoped that this counseling can increase community representation in development in Kedah.